14 Age and sex associations with myocardial extracellular volume in healthy mid-life adults. (17th November 2015) - Carberry, J; Carrick, D; Haig, C; Rauhalammi, S; Mangion, K; Corcoran, D; Radjenovic, A; Berry, C
Abstract : Background: Myocardial extracellular volume (ECV) can be estimated by cardiac magnetic resonance imaging (CMR). The age- and sex- associations with ECV in healthy mid-life adults are uncertain. Methods: Healthy adults with no cardiovascular disease underwent CMR at 1.5 Tesla (Siemens MAGNETOM Avanto). T1 mapping with MOLLI was performed before and 15-minutes after contrast (0.15 mmol/kg gadoterate meglumin). ECV was estimated in regions (AHA 16-segment model). ECV was calculated as the difference in relaxation rate (R1 = 1/T1) for myocardium and LV blood pool before vs. after gadolinium contrast administration, corrected for haematocrit (HCT). LV segments which were not evaluable due to artefact were excluded from analysis. Results: 120 segments were assessed from 20 subjects (mean age 61 ± 12 years; 11 (55%) male). 23(19%) segments were excluded due to artefact. The remaining segments for each subject were averaged to give an overall ECV (global LV). The mean (SD) ECV for all subjects was 22.2(3.1)%. ECV in females was higher than in males (24.4(3.2)% vs. 20.4(1.4)%; P = 0.006). Overall, ECV was negatively correlated with age (r = –0.455, P = 0.044), however, the correlation was sex-dependent (women: r = –0.666, P = 0.050; men: r = –0.131, P = 0.702). There was a statistically significant interaction between age and sex when assessed using linear regression (P = 0.029). Conclusion: Myocardial ECV is higher in women than in men. ECV is negatively correlated with age in women but not in men. The sex difference became less apparent with increasing age, implying that menopausal changes may be relevant. This possibility merits further assessment in a larger population.